KUALITAS APBD MENURUT PERSPEKTF PARTISIPASI MASYARAKAT DAN TRANSPARANSI KEBIJAKAN PUBLIK - Sri Dewi Anggadini; Tatik Rohmawati; Sari Damayanti; Ari Bramasto (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2021)
This study aims to find out the implementation of community participation and transparency of public policy on the quality of regional budget (APBD) in the South Coastal District Health Office. factors tested in this study are Community Participation and Public Policy Transparency as independent variables. While the quality of APBD as a dependent variable. The method used in this research is descriptive method. The population in this study is all employees of the Sub Division of Finance and Sub Division of Programs and Budget of the South Coast District Health Office. The sampling technique used is using census method (saturated sample), so that the number of samples used is 36 sample data. The data collection method is carried out by distributing questionnaires to employees of the Sub Division of Finance and the Program and Budget Sub-Section of the South Coastal District Health Office. The results showed that the Implementation of Community Participation and Transparency of Public Policy on the Quality of APBD in the South Coastal District Health Office is quite good but not fully optimal, where there is still a lack of participation and transparency carried out. Keywords: Transparency of Public Policy, Public Participation, Quality of APBD